Virtual reality-based interventions, a neoteric approach for management and rehabilitation in patients with breast cancer - Qurat-Ul-Ain Mohib; Lubna Vohra; Sana Zeeshan (Journal of the Pakistan Medical Association, 2024)
Breast cancer (BC) patients and survivors can experience immense emotional and psychosocial trauma. Treatment modalities for BC, including surgery, chemotherapy and radiotherapy are associated with certain displeasing and undesirable effects, including physical restrictions as well as mental stress. However, it has been ascertained that appropriate supportive and rehabilitative strategies can significantly help to alleviate the distress. Along with several conventional physical therapy options, the novel Virtual Reality (VR) tool has opened a new gateway in rehabilitative approaches in patients with BC. We reviewed the role of VR based management for BC-related incapacitations and found that its efficacy is comparable to that of contemporary therapy options. It has the additional benefits of modulating pain perceptions, improving mobility, and overall enhancing the quality of life of BC survivors. Keywords: Breast Neoplasms, Pain Perception, Physical Therapy, Virtual Reality, Rehabilitation, Cancer survivors